High-Yield Uniform Synthesis and Microstructure-Determination of Rice-Shaped Silver Nanocrystals. - Hongyan Liang; Huaixin Yang; Wenzhong Wang; Jianqi Li; Hongxing Xu (Journal of the American Chemical Society, 2009)
The article presents a study that assesses the high-yield uniform synthesis and microstructure of silver nanocrystals. The study was conducted by assessing the intrinsic properties of metal nanostructures along with its impact on size, shape, crystallinity and structural composition for the optimization of its optical properties. The study reveals that uniform silver nanorices can undergo synthesis based on polyol process due to its high visibility and anisotropic level.